Subjectivity at work in question - Sznelwar, Laerte Idal; Uchida, Seiji; Lancman, Selma (Tempo Social, 2011)
This paper examines the question of subjectivity in the workplace and the central role of work in the construction of subjects and their mental health, in light of advances in the psychodynamics of work. One of the most recurrent issues appearing in studies and initiatives in this field is the invisibility of work, the lack of recognition from others, especially corporate hierarchies. Different ways of organizing work privilege distinct and partial views of people, ignoring the existence of the subject. The concept of pathic rationality helps distinguish a view of the worker's subjectivity in which lived experience is central. The subject looks for meaning in a process of self-realization within a collective, striving to ensure that the end results of the work are as good as possible.